The Influence Of Changes In The Coretax Taxation System On Stress Levels And Workload In The Tax Department - Setiadi, Tri Budi; Saluy, Ahmad Badawi (Jurnal Fokus Manajemen, 2025)
This research aims to understand the perception of changes in the tax system based on Coretax on the stress levels and workload of employees working in the tax department. Coretax is a new taxation system implemented to improve the efficiency of tax administration in Indonesia. However, the transition to this new system can affect the psychological condition of workers, especially in the tax department who must adapt to these changes. The method used is a descriptive qualitative approach. Where this method is derived directly from primary data resulting from complaints from tax workers recorded in the industrial taxpayer group. The results of this study indicate that changes in the tax system can increase stress levels and add to the workload because other tasks are neglected due to excessive focus on the success of the system.